2008
DOI: 10.1063/1.2936306
|View full text |Cite
|
Sign up to set email alerts
|

High strength and utilizable ductility of bulk ultrafine-grained Cu–Al alloys

Abstract: Lack of plasticity is the main drawback for nearly all ultrafine-grained ͑UFG͒ materials, which restricts their practical applications. Bulk UFG Cu-Al alloys have been fabricated by using equal channel angular pressing technique. Its ductility was improved to exceed the criteria for structural utility while maintaining a high strength by designing the microstructure via alloying. Factors resulting in the simultaneously enhanced strength and ductility of UFG Cu-Al alloys are the formation of deformation twins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…in Cu-8 at% Al alloy) to several ten nanometers during severe plastic deformation (SPD) [3][4][5][6]. In some nanocrystalline (NC) face-centered-cubic (FCC) alloys a combination of both high strength and good ductility has been realized by tailoring their SFEs [5,[10][11][12][13][14][15][16][17][18][19]. These experimental results indicated that the SFE was an important factor influencing the grain refinement and mechanical behaviors of NC materials.…”
Section: Introductionmentioning
confidence: 82%
“…in Cu-8 at% Al alloy) to several ten nanometers during severe plastic deformation (SPD) [3][4][5][6]. In some nanocrystalline (NC) face-centered-cubic (FCC) alloys a combination of both high strength and good ductility has been realized by tailoring their SFEs [5,[10][11][12][13][14][15][16][17][18][19]. These experimental results indicated that the SFE was an important factor influencing the grain refinement and mechanical behaviors of NC materials.…”
Section: Introductionmentioning
confidence: 82%
“…Previous research [29] showed that lowering the SFE can increase the activation energy to some extent and lead to an increase in the instinct parameter ln(Z), which consequently increase the tendency to substitute deformation twinning for cross slip and suppress the dislocation activities. Profuse deformation twins are universally observed in SPD metals with low SFE [3,17,43,44], a high density of twins formed in SMAT-ed Cu-Al samples with low SFE is predictable. Deformation twins are effective in reducing the dislocation recovering and improving the dislocation storage capacity.…”
Section: The Activation Volume and Exhaustion Of Mobile Dislocationmentioning
confidence: 93%
“…Likewise, the strength and ductility can be improved simultaneously by decreasing the SFE in Cu-Al alloys [10], Cu-Zn alloys [19,20]. The enhancement of strength results from the formation of twins, stacking faults (SFs), microscale shear bands and their interaction, and incremental ductility is attributed to the recovery of the strain hardening rate by suppressing dynamic recovery through developing profuse twins and SFs that hinder the activities and annihilation of dislocations [14,21,22].…”
Section: Introductionmentioning
confidence: 97%